Using modified information delivery to enhance the traditional pharmacy OSCE program at TMU – a pilot study. (May 2018) - Lin, Che-Wei; Chang, Elizabeth H.; Clinciu, Daniel L.; Peng, Yun-Ting; Huang, Wen-Chen; Wu, Chien-Chih; Wu, Jen-Chieh; Li, Yu-Chuan
Highlights: Continuum of competency (one scenario – multiple continuous missions); 2) Traditional OSCE (one mission per station). Critical reasoning is difficult to teach and assess using only standardized patients and medical personnel – therefore iOSCE was developed as solution. Simulation modalities each has its own limitations, thus, we integrate the Virtual Patient in order to aid trainees during their assessment. Information technology (e.g. VP) can offer solutions for healthcare education by enhancing critical thinking and clinical reasoning. Abstract: Background and Objective: Objective Structured Clinical Examination (OSCE) has been used in many areas of healthcare training over the years. However, it constantly needs to be upgraded and enhanced due to technological and teaching changes. We aim at implementing an integrative OSCE method which employs informatics via the virtual patient within the pharmacy education curriculum at Taipei Medical University to enhance the pharmacy students' competence for using and disseminating information and to also improve critical thinking and clinical reasoning. Methods: We propose an integrated pharmacy OSCE which uses standardized patients and virtual patients (DxR Clinician). To evaluate this method, we designed four simulated stations and pilot tested with 19 students in the first year of the Master in Clinical Pharmacy program. Three stations were simulated as the inpatient pharmacy: 1) History and lab data collection; 2) Prescription review; 3) Calling physician to discuss potential prescription problems. The fourth was simulated as the patient ward station to provide patient education. A satisfaction questionnaire was administered at the end of the study. Results: Students rated their ability of 2.84, 2.37, 2.37, and 3.63 of 5 for each of the four stations, with the second and third being the most difficult stations. The method obtained an average rating of 4.32 of 5 for relevance, 4.16 for improving clinical ability, 4.32 for practicality in future healthcare work, and 4.28 for willing to have another similar learning experience. Conclusion: The integration of Virtual Patient in this study reveals that this assessment method is efficient and practical in many aspects. Most importantly, it provides the test taker with a much closer real-life clinical encounter. Although it is in many ways more difficult, it also provides for better "learning from mistakes" opportunities for test-takers.